Enfoque de enfermería en el cuidado espiritual del paciente con enfermedad renal crónica - Gómez Narváez, Aracely Elizabeth (2022)
ABSTRACT The objective of this research work was to determine the nursing actions in spiritual care in patients with chronic kidney disease. Chronic kidney disease produces the progressive loss of its function, for this reason patients need comprehensive care, changes occur: physical, psychosocial, cultural, environmental and especially in the spiritual aspect. Spirituality has not been defined within the field of health, however, the World Health Organization refers to it as a fundamental axis to provide quality care and warmth to patients; The spiritual dimension, according to the nursing approach, is the vital resource available to the patient to face suffering, the evolution of the disease and its consequences, thus improving their quality of life. A documentary-type investigation was carried out through the search based on the proposed theme, 114 selected documents were obtained as a search, taking theses, guides, scientific articles, which after applying inclusion and exclusion criteria, 66 bibliographic sources were obtained. The analysis for the development of the research was developed through a review, critical reading and triangulation of the information obtained from the different authors, which mention interventions that were classified according to the 8 spiritual care needs of Gregoriana Mendoza as: recognize the patient as a biopsychosocial being, provide empathic communication between the nurse/patient-family, promote resilience, apply the meditation technique, offer hospitality, hope and compassion, implement music therapy sessions, join support groups and facilitate spiritual growth; that allow positive compliance to treatment and adaptation to the disease. It was concluded that spiritual care in patients with chronic kidney disease is aimed at cultivating spirituality through the development of the therapeutic relationship in which the nurse / or - patient intervenes, facilitating a better lifestyle that includes: relief, well-being, emotional, psychosocial and family support aimed at stabilizing the patient's state of health. Finally, it was proposed to develop research related to spiritual care in order to socialize health personnel, which can be implemented in daily practice with the patient at an intramural or extramural level, verifying its effectiveness for evaluation through a randomized controlled method. Keywords: Chronic kidney disease, spirituality, spiritual, chronic diseases, nursing care, interventions.